Green growth dynamics: unraveling the complex role of financial development and natural resources in shaping renewable energy in Sub-Saharan Africa - Alhasan Osman; Mohd Afjal; Majed Alharthi; Mohamed Elheddad; Nassima Djellouli; Zhang He (Humanities & Social Sciences Communications)
Abstract This study examines the complex interplay between financial development, natural resources, and renewable energy consumption in Sub-Saharan Africa from 2000 to 2020, highlighting the pivotal role of financial strategies in enhancing sustainable energy practices. Employing an array of analytical techniques, including panel-corrected standard errors (PCSE), fixed effects, random effects models, and panel-fixed quantile regression, we delve into the nuanced relationships among these critical variables. The findings reveal that while natural resources and financial development generally exert negative impacts on renewable energy consumption when considered in isolation, a significant transformation occurs when these factors interact. Specifically, the detrimental effects of natural resources on renewable energy usage are substantially mitigated by robust financial development, which not only offsets the negative impacts but also promotes renewable energy adoption. This interaction points to a synergistic relationship where strategic financial development can leverage natural resources for progressive energy outcomes. Such insights underscore the necessity of well-coordinated financial policies and resource management to foster green growth in Sub-Saharan Africa, demonstrating the urgent need for integrated approaches to achieve sustainability in the region. This research not only clarifies the dynamics of financial and natural resource interdependencies but also motivates significant policy implications for enhancing renewable energy landscapes in developing economies.